Konstruksi dan Ekspresi Identitas: Studi tentang Pembentukan Identitas Ke-Papua-an di -Yogyakarta - , MOH RAFLI ABBAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Identity is a social construction. Ethnicity is an expression of the product's past, the resurrection of the same origin, social relationships, and similarities in cultural values and characteristics such as language and religion. It further explained that the historical dimension of identity showed that identity is uncertain, it is not constant, and not eternal, but sometimes change and can be shaped or constructed. Many factors can be influential in the construction of identity, as well as religion, power, politics, and more. This research was conducted with the aim to